Metabolic profiles of cysteine, methionine, glutamate, glutamine, arginine, aspartate, asparagine, alanine and glutathione in Streptococcus thermophilus during pH-controlled batch fermentations - Yali Qiao (Nature Portfolio, 2018)
Abstract Elucidating the amino acid (AA) metabolism patterns of Streptococcus thermophilus has important effects on the precise design of nitrogen sources for high-cell-density culture. Transcriptomics and metabolomics were combined to reveal the cysteine, methionine, glutamate, glutamine, arginine, aspartate, asparagine and alanine metabolic pathways in S. thermophilus MN-ZLW-002, including glutathione. The changes in the synthesis, consumption and concentration of AAs and their metabolites, as well as regulatory genes with time were revealed. The metabolism of L-cysteine, L-glutamate, L-aspartate and L-alanine generated some potential functional metabolites. The metabolism of methionine and glutamate generated potential harmful metabolites. S. thermophilus MN-ZLW-002 can synthesize glutathione. Some potential functional metabolites have similar biological functions, indicating that S. thermophilus can resist environmental stresses through multiple mechanisms. The expression of some key genes in synthesis pathway of AA indicated that cysteine, methionine, asparagine, aspartate, arginine and lysine were insufficient or imbalance between nutrient components. The accumulation of large amounts of AA metabolites might be the primary cause of the overconsumption of AAs and influence the growth of S. thermophilus. The present study revealed the metabolic profiles of abovementioned AAs as well as those of regulatory genes and metabolites. These results were beneficial to the precise design of nitrogen sources and regulation of functional metabolites for the high-cell-density culture of S. thermophilus.